ОСОБЛИВОСТІ ГОТОВНОСТІ ВИХОВАТЕЛІВ ДО ДІЯЛЬНОСТІ У СУЧАСНОМУ ДОШКІЛЬНОМУ НАВЧАЛЬНОМУ ЗАКЛАДІ (Педагогіка вищої та середньої школи, 2007)
The article covers of the contemporary the issues of the professional activities the tutors in the pre-school establishment. The analysis the program is on the pre-school education show oneself importance to be ready of the upbringing of responsibility of the person under-fives.